AVALIAÇÃO DAS PROPRIEDADES MECÂNICAS E QUÍMICAS DE RESINAS BIOATIVAS EXPERIMENTAIS PARA A COLAGEM DE BRÁQUETES. - FREITAS, Mariana Almeida Mello Proença de (2018)
Objective: To develop and characterize experimental materials containing different concentrations of niobophosphate (NbG) and 45S5 glass used for bonding of brackets: pH, microhardness, bioactivity, bond strength and fracture mode (ARI). Materials and Methods: Experimental resins (NbG 5%, NbG 10%, NbG 20%, 45S5 5%, 45S5 10% and 45S5 20%) were used, an experimental resin without bioactive glass and a commercial resin (Transbond XT) were also used. evaluated. To evaluate the ability to neutralize / alkalize, resin discs (15 mm diameter and 1.3 mm high) were made and immersed in two pHs (4 and 7) and pH measurements were analyzed in the 24h, 7d , 14d and 28d (n = 4). The resulting solution was subjected to inductively coupled plasma atomic emission spectrometry (ICP-AES) to analyze the release of Ca ++ and PO4-3 ions. To evaluate Knoop microhardness of the materials, specimens were made and taken to a microdurometer. To evaluate the bioactivity, resin disks were prepared and maintained in PBS for 28 days and taken for analysis in SEM and FTIR / ATR (n = 4). Metallic brackets were bonded to human premolars (n = 10) and subjected to a Des-Re cycling for 8 days. After this period, the bond strength was evaluated in a universal test machine (Instron 3342). The fracture mode (IAR) was evaluated in a stereomicroscope at a magnitude of 10x. To determine statistically significant differences the data from each test were submitted to appropriate statistical analysis. Results: Experimental resins containing 45 S5 showed the ability to raise the pH of the solution, regardless of the initial pH and bioglass concentration in the material. The other resin (NbG, Control and Transbond XT) presented a neutralizing potential only for the initial pH 4. Transbond XT resin at initial pH 7 reduced the pH to an acidic condition (pH = 5.7) after 28 days. The release of calcium and phosphorus ions was most notably present in solutions of pH = 4. Phosphorus release was low in the most of resins. The resins without bioactive glasses (Transbond XT and Control) did not present release of calcium and phosphate ions. Transbond XT shows high microhardness when compared to experimental resins (P <0.05). SEM analysis showed surface precipitates of resins containing bioactive glasses. These images agree with the results obtained in the FTIR / ATR analysis, where calcium phosphate peaks were observed. Transbond XT and control resins did not show precipitate formation after the 28 day period. There was no difference in bond strength between the materials tested. The Transbond XT showed a tendency of ARI = 2, while the other resins showed predominance of ARI = 0. Conclusion: Resins containing bioactive glass showed a bond strength equal to that of the resin considered to be market standard, with the advantage of leaving residual adhesive in a reduced quantity. In addition, the low hardness presented by these resins may be a good feature, facilitating the removal of the remaining adhesive. Resins containing 45 S5 in their various concentrations showed a high capacity to raise the local pH and released calcium and phosphorus ions. The formation of precipitates on the surface of the material may be indicative of their bioactivity.